Efficacy of Lactobacillus Administration in School-Age Children with Asthma: A Randomized, Placebo-Controlled Trial - Chian-Feng Huang; Wei‐Chu Chie; I‐Jen Wang (2018)
Probiotics may have immunomodulatory effects. However, these effects in asthma remain unclear and warrant clinical trials. Here, we evaluated the effects of Lactobacillus paracasei (LP), Lactobacillus fermentum (LF), and their combination (LP + LF) on the clinical severity, immune biomarkers, and quality of life in children with asthma. This double-blind, prospective, randomized, placebo-controlled trial included 160 children with asthma aged 6–18 years (trial number: NCT01635738), randomized to receive LP, LF, LP + LF, or a placebo for 3 months. Their Global Initiative for Asthma–based asthma severity, Childhood Asthma Control Test (C-ACT) scores, Pediatric Asthma Severity Scores, Pediatric Asthma Quality of Life Questionnaire scores, peak expiratory flow rates (PEFRs), medication use, the levels of immune biomarkers (immunoglobulin E (IgE), interferon γ, interleukin 4, and tumor necrosis factor α) at different visits, and the associated changes were evaluated. Compared with the placebo group by generalized estimating equation model, children receiving LP, LF, and LP + LF had lower asthma severity (p = 0.024, 0.038, and 0.007, respectively) but higher C-ACT scores (p = 0.005, < 0.001, and < 0.001, respectively). The LP + LF group demonstrated increased PEFR (p < 0.01) and decreased IgE levels (p < 0.05). LP, LF, or their combination (LP + LF) can aid clinical improvement in children with asthma.